Structure Based Design And Synthesis Of Potential Dengue Virus NS2B-NS3 Protease Inhibitors - Sinha,, Suman (2018)
Dengue is transmitted by the bite of a mosquito infected with one of the five dengue virus serotypes. As far as anti-dengue drug discovery is concerned, among few established therapeutic targets, NS2B-NS3 protease is quite popular due to its role in production of mature viruses and plays a key role in maintaining infectivity. The work in this thesis described the computational and experimental studies in the design and synthesis of novel NS2B-NS3 protease from natural scaffolds such as lawsone and ferulic acid. In the case of naphthoquinone class of compounds, it was understood from docking studies that incorporation of molecular flexibility could lead to tighter binding compounds.